Pengaruh Persepsi Konsumen Dan Motivasi Konsumen Terhadap Keputusan Pembelian Kartu Indosat Ooredoo (Studi Kasus Masyarakat Harjosari 1 Kec. Medan Amplas) - Sartika Sartika; Muhammad Radiansyah (Al-Sharf: Jurnal Ekonomi Islam, 2022)
The purpose of this study was to determine how much influence consumer perception and consumer motivation simultaneously on purchasing decisions of Indosat Ooredoo cards. This study uses a quantitative approach which is carried out by testing research variables through the formation of an analytical model with statistical procedures which are then taken as a basis for interpretation of conclusions. The population in this research is the entire community in Harjosari 1 as many as 1085 people with a sample = 100 people. The instrument in this study was a questionnaire or questionnaire. The data analysis technique used in this research is multiple linear regression analysis. Based on the results of the t-test calculation, it is known that the consumer perception variable obtained tcount > ttable (6.560> 1.985) with a significant 0.00 < 0.05. This proves that consumer perceptions have a significant effect on purchasing decisions. The variable of consumer motivation obtained tcount > ttable (2,368 > 1,985) with a significance of 0.02 < 0.05. This proves that consumer motivation has a significant effect on purchasing decisions. Based on the results of the simultaneous test (F test) obtained Fcount > Ftable (44.199 > 3.09) with a sig level of 0.000 > 0.05. This shows that the variables of consumer perception and consumer motivation simultaneously have a positive and significant effect on the purchasing decision variables. Based on the results of the coefficient of determination, it is known that the R square value is 0.577. This means that the influence of consumer perceptions and consumer motivation on purchasing decisions is 57.7%, while the remaining 42.3% is influenced by other variables not included in this study.